PERFOMNCE, INTESTINE MORPHOLOGY AND SERUM BIOCHEMISTRY OF BROILER CHICKENS TO DELAYED POST HATCH FEEDING - MUSTAFA, MERKHAN M. (Journal of Duhok University, 2021)
This study was conducted to estimate the effect of delayed post hatch feeding after arrival to the rearing hall on broiler performance, serum biochemistry and jejunum histology. A total of 225 Ross 308 day-old chicks were randomly distributed into three groups T1 chicks access to feed immediately, T2 chicks delayed in feeding for 12 hours and T3 chicks delayed in feeding for 24 hours with three replicates of 25 chicks. Remained yolk sack was lower for chicks that had immediate access to feed compared to other experimental groups. Longer delay feeding time lowered body weight uniformity % at different ages. Immediate access to feed significantly (P<0.05) improved broiler performance at different ages compared to that delayed for 12 and 24 hours post hatch. Significantly (P<0.05) longer small intestine and higher percent of live body weight were recorded for early feeding groups compared to delayed groups. The level of T3 and T4 hormones in the serum were significantly (P<0.01) higher for early feeding groups compared to other groups. Increasing delayed post hatch feeding led to a significant (P<0.01) increase in uric acid level in serum. Early feeding significantly (P<0.01) improved jejunum histology including villi height, villi width, villi height to crypt depth and surface area